Fathering on Tenuous Ground: A Qualitative Meta-Synthesis on Teen Fathering. Issue 4 (July 2019) - SmithBattle, Lee; Phengnum, Wisitsri; Shagavah, Anne Winnie; Okawa, Satoko
Abstract: Background: Although teen fathers are a vulnerable group of parents, they have received far less attention than teen mothers. Purpose: We conducted a systematic search of qualitative studies that examined their prenatal and postpartum experience to better understand teen fathers' concerns, strengths, and vulnerabilities. Methods: We searched nine electronic databases through September 2017; 29 studies represented in 30 articles met study criteria. All authors independently extracted data from each article. Coding decisions were reviewed weekly and differences were settled by consensus. Results: From pooling the results of 29 primary studies, we describe how a tenuous ground contributes to teen paternity and imperils young fathers' involvement with their children. In the best of circumstances, the ground begins to stabilize for teens who become involved parents despite significant challenges and hardships. Clinical Implications: Our results contribute to the visibility of teen fathers and the social disparities that imperil fathering. We provide clinical guidance for strengthening the ground for teen fathers and their families, recognizing that clinicians often encounter challenges such as interpersonal factors and sociocultural conditions that systematically erode fathers' ties to their children, partners, professional caregivers, and institutions. Abstract : In this meta-synthesis, Dr. Lee SmithBattle, who has been studying teen pregnancy for many years, and her colleagues, reviewed studies on teen fathering. Based on their analysis, teen fathering can be quite challenging. Many factors imperil young fathers' involvement with their children, however becoming a father engenders a new identity anchored by paternal responsibilities. Nurses can use these findings to further their understanding of teen fathering and offer their support.